Design and Implementation of Next Generation Automotive Theft Preventive System - K. Hema; Muralidharan Muralidharan (Institute of Advanced Engineering and Science, 2018)
In this paper, we proposed to design a next-generation auto theft prevention system by adding significant enhancements and modernizing the existing security features. As vehicles turn out to be more refined, vehicle security frameworks must be more grounded than at any other time. A current vehicle uses remote keyless passage framework and Immobilizer framework as the primary weaponry against vehicle robbery. These structures avoid unapproved access of the vehicle to a particular degree, however, are not a secure one. Because of the straightforward and imperfect nature of these security frameworks, auto burglary occurrences worldwide are on the ascent. This venture needs a low power microcontroller however with elite prerequisites. LPC11C14 from NXP Semiconductors addresses these issues and in this manner picked as the primary MCU. It is an ultra-low-power ARM Cortex-M0 based microcontroller that can run up to 50MHz. It has 32KB of Flash memory and 8KB RAM.